2011
DOI: 10.1007/s12098-011-0457-2
|View full text |Cite
|
Sign up to set email alerts
|

Billateral Polycystic Kidneys in a Girl with WAGR Syndrome

Abstract: The WAGR contiguous gene deletion syndrome is a combination of Wilms tumor, aniridia, genito-urinary abnormalities, and mental retardation. An 8.5-year-old girl was initially investigated at the age of 18 months for congenital bilateral aniridia, cataracts, glaucoma and epicantus. The ultrasound (US) scan showed polycystic kidney disease. FISH study revealed deletion of the WT1 and PAX6 gene in the 11p13 WAGR region. Forty days after the first kidney US, the second US revealed a 3 cm tumor in the right kidney:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…WAGR syndrome includes WT, genitourinary anomalies, aniridia, and intellectual disability. WT developed in the right kidney, and the child was treated with nephrectomy followed by chemotherapy ( 13 ). In our clinical case, the girl also has dysmorphic facial features but was not diagnosed with any additional genetic syndrome during exome testing.…”
Section: Discussionmentioning
confidence: 99%
“…WAGR syndrome includes WT, genitourinary anomalies, aniridia, and intellectual disability. WT developed in the right kidney, and the child was treated with nephrectomy followed by chemotherapy ( 13 ). In our clinical case, the girl also has dysmorphic facial features but was not diagnosed with any additional genetic syndrome during exome testing.…”
Section: Discussionmentioning
confidence: 99%
“…Gucev et al . 24 reported an 8.5-year-old patient with WAGR syndrome, which includes Wilms tumor, and bilateral PKD. Zina et al .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, despite not being a recurrent observation in patients with 11p deletion, polycystic kidneys were identified in patients P4 and P10, also diagnosed with Wilms' tumor. Gucev et al [2011] reported a case of WAGR syndrome with bilateral polycystic kidney. The presence of multiple renal cysts can be attributed to several genes such as PAX2, PKD1, PKD2, and HNF1B [Eneman et al, 2014], none of which is mapped in the short arm of chromosome 11.…”
Section: Other Nonclassical Phenotypes Observed In 11p Deletionsmentioning
confidence: 99%